Comparison of Different Adhesive Systems on Bond Strength of Resin Composite Posts Placed in Primary Teeth - Zahra Bahrololoomi; Fateme Mehravar (International Journal of Dentistry)
Background. This study evaluated the push-out bond strength of resin composite posts to the intracanal dentin in primary teeth using different adhesive systems. Materials and Methods. In this experimental study, sixty-eight primary lateral incisors were randomly allocated in four groups (n = 17): Adper Single Bond 2 (ASB), Clearfil SE Bond 2 (CSE), G-Premio Bond in etch-and-rinse mode (GP-ER), and G-Premio Bond in the self-etch mode (GP-SE). The coronal one third of root canals was filled with resin composite. The push-out test was performed using a universal testing machine. ANOVA and LSD tests were used to analyze the data (P<0.05). Results. One-way ANOVA showed significant differences between the four groups in push-out bond strength (P=0.002). The ASB and GP-SE groups showed lower and higher bond strengths, respectively. The failure mode distribution did not differ between the bonding agents used (P=0.763). Adhesive and mixed failures were more frequent. Conclusion. The GP-SE, GP-ER, and CSE exhibited significantly higher push-out bond strength than ASB. A universal adhesive system and 6th generation self-etch adhesives are recommended for use with resin composite posts in primary anterior teeth. Regarding the advantages of these bonding agents, such as fewer clinical steps, lower technical sensitivity, and easy application, they can be a good option for restoring primary teeth with short resin composite posts.